How to Keep Your Food Supply Chain Fresh - Munson, Chuck (Charles Lee); McNamara, Tom; Marsillac, Erika (Pearson, 2013)
This new case study examines supply chain issues faced by food retailers as consumers demand greater variety, more fresh produce, and year-round access to exotic products--ranging from Fair Trade coffee from Bali to fresh-cut roses from Kenya. It discusses what managers must do to manage increased supply chain complexity, use real-time data more effectively, forecast and model more accurately, and make better decisions when the cost of mistakes can be catastrophic. Throughout, it focuses on realistic issues and challenges, offering exceptional value to both students and practitioners. Authors: Tom McNamara, ESC-Rennes; Erika Marsillac, Old Dominion University.